Topology Design of Modular Unit and Cable Network of On-Orbit Modular-Assembled Antenna - Huanxiao Li; Shengnan Lyu; Xiaofei Ma; Kunyang Lin; Dayu Zhang; Xiaotao Zhou; Guanlong Su; Yang Li; Xin Jin (International Journal of Aerospace Engineering)
With the increasing demands of ultra-large space antennas, on-orbit assembly stands out as a promising solution. However, this achievement necessitates the reconfiguration design of the whole antenna structure to maintain structural integrity and stability. In light of this challenge, a novel rapid design method is proposed for the unit configuration of modular-assembled antennas in this paper. The method utilizes an inscribed regular hexagon, which is positioned within a horizontal topological circle. The hexagon is subsequently projected onto a spinning paraboloid, resulting in the creation of unit nodes that conform to the shape of the paraboloid. The configuration of the unit topology is then determined based on the arrangement of these nodes. By using the method, two units of space-assembled antennas are designed. The topology design of the cable network is carried out for the modular unit. The pretensions of the cables are calculated. The results of the case study reveal that the developed modular units fulfill the requirements of the on-orbit-assembly antenna structure and can solve the engineering application difficulties of this type of antenna.